(untitled) (Politeja, 2023)
ISLAMIC REPUBLIC OF IRAN TOWARDS CENTRAL AND EASTERN EUROPE UPON THE BACKGROUND OF THE WAR IN UKRAINE The article attempts to analyze the politics of the Islamic Republic of Iran towards the Central and Eastern Europe during the war conflict in Ukraine, 2022. The aim of the study is to describe the tactic and strategic approach of the IRI to the abovementioned problem in order to answer the question about the power shift in Central Asia. An additional aim is to show the image of the USA and NATO as created by the IRI, and to point to the role of Poland in the IRI’s tactical actions to sustain positive relations with Europe. The role of Russia, one of the most influential actors both in the European and in the Eurasian areas cannot be omitted.